The The first transcanal endoscopic ear surgery in Udayana University General Hospital - Danastri, I Gusti Ayu Mahaprani; Lolik Lesmana, I Wayan; Pranitasari, Ni Putu Oktaviani Rinika; Raditya, I Gede Wahyu Adi; Pradiptha, I Putu Yupindra; Wahyu Widiantari, I Gusti Ayu Putu; Nogueira, João Flávio (PERHATI-KL, 2024)
Background: The conventional method for treating cholesteatoma involves using a microscopicapproach. However, over the years, endoscopy has evolved from being a supplementary tool alongside themicroscope to becoming the primary transcanal approach in different areas of ear surgery. Purpose: Topresent a case of cholesteatoma in adult which was treated by the combination of transcanal endoscopicear surgery and mastoidectomy. Case report: An adult patient with malignant type of chronic suppurativeotitis media underwent transcanal endoscopic ear surgery and mastoidectomy. Endoscopic surgery is amore intricate single-handed procedure that demands both experience and a comprehensive knowledge ofendoscopic ear anatomy. This is essential for navigating the anatomical space, dealing with the ossicularchain, and employing transcanal drilling techniques. The primary surgical focus for endoscopic earsurgery is the middle ear. When addressing cases where cholesteatoma extends beyond the posteriorepitympanum, the surgical approach relies on the surgeon’s expertise in performing extensive atticotomyor mastoidectomy, either with or without microscope assistance. Clinical question: What is the role oftranscanal endoscopic ear surgery and mastoidectomy in adult patient with cholesteatoma? Method:Literature searching was performed with the keywords: ”cholesteatoma”, AND ”transcanal endoscopicear surgery”, AND ”mastoidectomy” through database PubMed, Proquest, and hand searching/e-book. Result: There were 3 articles relevant with the subject. Conclusion: Transcanal endoscopic ear surgery isa minimally invasive and secure procedure characterized by its low rates of complications and recurrence Keywords: transcanal endoscopic ear surgery, mastoidectomy, cholesteatoma, chronic suppurative otitis media.